2010
DOI: 10.1016/j.neurobiolaging.2008.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E mediates sulfatide depletion in animal models of Alzheimer's disease

Abstract: Herein, we tested a recently-proposed working model of apolipoprotein E (apoE)-mediated sulfatide metabolism/trafficking/homeostasis with two well-characterized amyloid precursor protein (APP) transgenic (Tg) animal models of Alzheimer’s disease (AD) (i.e., APPV717F and APPsw) on a wild-type murine apoE background or after being bred onto an Apoe−/− background. As anticipated, lipidomics analysis demonstrated that the sulfatide levels in brain tissues were reduced beginning at approximately 6 months of age in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 40 publications
(77 reference statements)
9
71
0
Order By: Relevance
“…4 ). Our previous studies showed that the expression as well as haplotype of apoE has a close association with sulfatide homeostasis ( 20,(37)(38)(39). Additionally, it has been found that long-term CR can lead to alterations in the expression of apoE in brain ( 40 ).…”
Section: Depletion Of Sulfatide Content In Pgc-1 ␣ ؊ / ؊ Cortex Was Nmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ). Our previous studies showed that the expression as well as haplotype of apoE has a close association with sulfatide homeostasis ( 20,(37)(38)(39). Additionally, it has been found that long-term CR can lead to alterations in the expression of apoE in brain ( 40 ).…”
Section: Depletion Of Sulfatide Content In Pgc-1 ␣ ؊ / ؊ Cortex Was Nmentioning
confidence: 99%
“…Proteins were transferred to an immobilon™-P membrane (Millipore) for 2 h at 80 V at 4°C. The immobilon™-P membrane was then washed with Tris-buffered saline (TBS) and blocked with 5% nonfat powdered milk in TBS with Tween 20, pH 7.6 for 1 h. Primary antibodies used were diluted as follows: myelin basic protein (MBP, 1:500, Millipore, MAB386); proteolipid protein (PLP, 1:4000, Novus Biological, NB100-74503); myelin-associated oligodendrocyte basic protein (MOBP, 1:1000, Santa Cruz, P18); glyceraldehydes 3-phosphate dehydrogenase (GAPDH, 1:2000, Santa Cruz, FL-335); cerebroside sulfotransferase (CST, 1:500, Sigma, HPA001220); arylsulsulfatase A (ASA, Our previous studies have showed that i ) the content of sulfatide (a class of myelin-specifi c sphingolipid) is dramatically depleted at the earliest clinically recognizable stages of AD (mild cognitive impairment ) in both postmortem brain ( 16,17 ) and freshly collected cerebrospinal fl uid of AD patients compared with age-matched cognitively normal controls ( 18 ); ii ) the sulfatide content in the central nervous system is modulated by apolipoprotein E (apoE) in an isoform-dependent manner through the same metabolic pathways that regulate apoE-associated particles ( 19 ); and iii ) apoE mediates sulfatide depletion in mouse AD models ( 20,21 ).…”
Section: Western Blot Analysis Of Wt and Pgc-1 ␣ ؊ / ؊ Corticesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in sulfatides, however, was obliterated following ApoE deletion in APP mice (Cheng et al, 2010), indicating that the reduction in sulfatides in APP mice is mediated by ApoE. The drop in sulfatide levels in the brain tissues of AD patients (Han et al, 2002;Bandaru et al, 2009) and AD mouse models (PS1, PS1/APP, APP) (Cheng et al, 2010;Chan et al, 2012) may be associated with oligodendrocytes death and myelin destruction, leading to a failure in maintaining the functional integrity of neurons in the afflicted individuals or animal models. On another note, plasmalogen ethanolamine (pPE) is a major constituent of human neural membranes.…”
Section: Lipid Changes In Relation To Neuronal and Synaptic Lossmentioning
confidence: 99%
“…Direct MS analysis on APP transgenic mouse cortex and cerebellum showed lower sulfatide levels (Cheng et al, 2010), while perturbations in homeostasis of lipids, energy management, and metabolism of amino acids and nucleotides were visible on APPxPS1 hippocampus and cortex (Gonzalez-Dominguez et al, 2015h). Employing ultra high resolution MS instruments, Lin et al, (2013) were able to observe over-production of eicosanoids indicating neuroinflammation on hippocampal tissues (Lin et al, 2013), and enhanced biosynthesis of amino acid and amino acid derivatives in cerebellum (Lin et al, 2014).…”
Section: Animal Models Of Admentioning
confidence: 99%